2005
DOI: 10.1016/j.physb.2004.11.087
|View full text |Cite
|
Sign up to set email alerts
|

Improving the understanding of the melting behaviour of Mo, Ta, and W at extreme pressures

Abstract: We discus existent conflicts between experimentally measured and theoretically calculated melting curves of Mo, Ta, and W. By assuming that vacancy formation plays a fundamental role in the melting process, an explanation for the measured melting curves is provided.Furthermore, we show that the Lindemann law fits well all the measured melting curves of bcc transition metals if the Grüneisen parameter is written as a power series of the interatomic distance. For completeness, we examine possible reasons for cur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
83
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 52 publications
12
83
3
Order By: Relevance
“…However, in the pressure range close to 100 GPa, there still exists large discrepancy in T m data measured between DAC [2-4, 16, 17] and SW [6] experiments. Furthermore, the dT m /dP behavior does not significantly change when P-T m locus evolves across the triple point of bcc-hcp-liquid, at about 210 GPa, conjectured by Errandonea [16] from Hixson's Hügoniot C measurements [7]. The melting curve in this work is against the twosegment melting curve model proposed by Errandonea [16].…”
Section: Melting Properties Of Mosupporting
confidence: 49%
“…However, in the pressure range close to 100 GPa, there still exists large discrepancy in T m data measured between DAC [2-4, 16, 17] and SW [6] experiments. Furthermore, the dT m /dP behavior does not significantly change when P-T m locus evolves across the triple point of bcc-hcp-liquid, at about 210 GPa, conjectured by Errandonea [16] from Hixson's Hügoniot C measurements [7]. The melting curve in this work is against the twosegment melting curve model proposed by Errandonea [16].…”
Section: Melting Properties Of Mosupporting
confidence: 49%
“…Using this technique, melting of Ta was detected in the pressure range from 250 to 300 GPa, with a calculated melting temperature of 7000-10000 K (Dai et al, 2009;Shaner et al, 1984). After applying a superheating correction, M T may be as low as 5000-8000 K (Errandonea, 2005;Errandonea, 2006;Luo et al, 2003). A linear extrapolation of the DAC data to 300 GPa, puts an upper limit of 4800 M TK  .…”
Section: Page 5 Of 16mentioning
confidence: 99%
“…Triangles: (Fatteva, et al, 1971). Calculated melting curves are included [FP (Taioli, et al, 2007) and QB (Moriarty et al, 2002)] together with the Lindemann (L) estimates (Errandonea, D., 2005).…”
Section: Page 9 Of 16mentioning
confidence: 99%
“…At low temperatures, Mo is stable in the body-centered-cubic (bcc) phase up to a pressure (P) of about 700GPa, where it transforms to fcc phase (Belonoshko, 2008). Considerable experimental and theoretical methods had been developed for Mo to study its thermodynamic properties such as melting temperature T m , thermal equation of state (EOS), Grüneisen parameter γ and Debye temperature Θ D , et al (Hixson, 1992;Zhang, 2008;Errandonea, 2005;Burakovsky, 2004;Kushwah, 2013;Zeng, 2011;Litasov, 2013;Al'tshuler, 1987;Asimow, 2009;Cazorla, 2007;Vinet, 1989). It's found that there exist great discrepancies in the melting curves between laser-heated diamond anvil cell (DAC) (Santamaría-Pérez, 2009) and shock-wave (SW) measurements (Hixson, 1992;Zhang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It's found that there exist great discrepancies in the melting curves between laser-heated diamond anvil cell (DAC) (Santamaría-Pérez, 2009) and shock-wave (SW) measurements (Hixson, 1992;Zhang, 2008). Errandonea (Errandonea, 2005) considered the following expression for the volume dependence of γ similar to that proposed by Burakovsky and Preston (Burakovsky, 2004 ):…”
Section: Introductionmentioning
confidence: 99%